Models of Financial Pyramids - Girdzijauskas, Stasys; Moskaliova, Vera (Ekonomika, 2003)
The financial structures that make use of money flow for “casy money” or cheating purposes arc called financial pyramids (FP). Recently financial pyramids intensively penetrates IT area. It is rather suitable way of the fraud. Money flow modelling and activity analysis of such financial systems allows identifying FP and taking necessary means of precautions. In the other hand even investing companies that function normally when market conditions changes (e. g. interest rate) eventually might become FP. Modelling of FP could be helpful for identifying signs of such instability. Goal of this article is creating of mathematical models and using them for researching of FP. The research methods applied arc literature analysis, generalization and mathematical modelling.